COMPARATIVE ANALYSIS OF THE EFFECTIVENESS OF VARIOUS BARIATRIC SURGERIES - Tukhtaev, D.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Obesity in the twenty-first century is becoming an epidemic and is a major cause for serious concern in both developed and developing countries. Morbid obesity negatively affects several body systems at the same time, and together with its accompanying complications, leads to an overall decrease in the expected quality. Worldwide, there are about a billion people who are overweight. About half of the population in industrially developed countries, except for Japan and China, is overweight. In many countries of the world, over the past 10 years, the incidence of obesity has increased by an average of 2 times. There is a steady increase in obesity among children. In the countries of the Commonwealth of Independent States, the prevalence of obesity and overweight is currently about 50%. WHO experts believe that by 2050, the entire population of economically developed countries of the world will have some degree of obesity. That is why in 1997 the WHO recognized obesity as a global epidemic of the twenty-first century. This review article is devoted to the features of the effectiveness of bariatric surgery in obese patients.